STRUGGLE FOR INDEPENDENCE AND THE EASTERN BORDER OF THE POLISH REPUBLIC (NOVEMBER 1918 – MARCH 1921). - BOYECHKO, V. F. (Вісник Черкаського університету. Серія: Історичні науки, 2017)
Introduction. The First World War led to the disintegration of multinational empires enhance national liberation movement of the Slavic peoples, which in turn led to an appearance on the political map of Europe, the new independent states that determined the nature of their political system as democratic. In this connection special importance is the study of the history of the formation and preservation of the struggle for the independence of Poland in 1918-1921 years. The worst of it was not only the economic survival of the restored state, but also the military defense of sovereignty and resolution of territorial conflicts. Purpose of the article is to explore the fight for the preservation of the independence of the Second Polish Republic and resolve territorial claims. Methods. Were used modern methods and achievements of historiography, source base to study the characteristics of the struggle for preserving the independence of the Polish Republic in 1918-1921. Author studied views Dmowski R. and J. Pilsudski to meet the local requirements of the eastern territories. Outlined evolution of leading European states on territorial separation from support Polish claims to the gradual containment of Polish territorial appetites. It was found that consistently Polish territorial interests protected France. Particular attention is paid to the process of diplomatic and military confrontation in Poland with Soviet Russia in defining the frontiers. Characterized forceful installation of power of the Polish government in Western territories, the peculiarities of military expansion of Poles in Belarus and Lithuanian lands in 1919-1920. Results and conclusion. Poland won the military and political struggle for the preservation of their sovereignty. Riga contract was profitable for Poland, saved independence, and territorial claims were satisfied. The defeat meant the end of plans Bolshevik Revolution and Communism exports to Western Europe. However, Poland received a large territory with a population that showed incorporative model of leader political party. Riga treaty became the basis for the request of Poland before international organizations regarding its rights to eastern Galicia and Volyn. On March 14, 1923 the Council of Ambassadors of the League of Nations adopted the decision to recognize the eastern border of Poland, agreeing thus with belonging Eastern Galicia, Volhynia, Western Belarus and Vilenschyny to the Polish state.